2020
DOI: 10.1007/s10549-020-05921-x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of pertuzumab plus trastuzumab and docetaxel as a first-line therapy in Japanese patients with inoperable or recurrent HER2-positive breast cancer: the COMACHI study

Abstract: Purpose In the CLEOPATRA study of patients with human epidermal growth factor receptor 2 (HER2)-positive recurrent or metastatic breast cancer, the Japanese patient subgroup did not demonstrate the improved progression-free survival (PFS) of pertuzumab plus trastuzumab and docetaxel vs. placebo that was seen in the overall population. Therefore, COMACHI was conducted to confirm the efficacy and safety of this treatment regimen in this patient subgroup. Methods This was a phase IV study of pertuzumab plus tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
4
6
1
Order By: Relevance
“…A previous Ontario study found 1.8 heart failure events that required hospitalization per 100 person-years among patients who received pertuzumab. 12 The percentage of patients who received pertuzumab and experienced cardiotoxicity-related adverse events in our study was similar to that in other studies, 10,16 which is also similar to the CLEOPATRA trial result of 3.8%. 15 The real-world definition of cardiotoxicityrelated adverse events we used was different from the definition used by the trial, which defined adverse events as more than a 10% point decline in left-ventricular ejection fraction at baseline, or to less than 50%, or if treatment was required.…”
Section: Discussionsupporting
confidence: 90%
“…A previous Ontario study found 1.8 heart failure events that required hospitalization per 100 person-years among patients who received pertuzumab. 12 The percentage of patients who received pertuzumab and experienced cardiotoxicity-related adverse events in our study was similar to that in other studies, 10,16 which is also similar to the CLEOPATRA trial result of 3.8%. 15 The real-world definition of cardiotoxicityrelated adverse events we used was different from the definition used by the trial, which defined adverse events as more than a 10% point decline in left-ventricular ejection fraction at baseline, or to less than 50%, or if treatment was required.…”
Section: Discussionsupporting
confidence: 90%
“…We analyzed the real-world, single center data from patients who underwent combination treatment with trastuzumab, pertuzumab, and docetaxel as a first-line chemotherapy for HER2positive MBC. Survival outcomes in this study were comparable to those of previous ones, including several studies using real-world data [12,[15][16][17]. In addition, in terms of ORR, our results were similar or better than those reported previously along with a higher CR rate of…”
Section: Discussionsupporting
confidence: 88%
“…All rights reserved. 17.9% [8,15]. Although safety outcomes in our study were consistent with those of previous studies, it should be considered that evaluation of toxicities was quite limited by the retrospective nature of this study.…”
Section: A C C E P T E D a R T I C L E Korean Cancer Associationsupporting
confidence: 89%
“…This finding was significant. Some traditional chemo drugs based on microtubule targeting agents, such as taxol, are associated with severe side effects [87,88], since all cells, healthy and tumor cells, need microtubule functions. Therefore, a variety of Eg5 inhibitors have been developed, a certain of them have entered clinical trials, including Arry-520 (Sponsor: Array Biopharma) [ [104].…”
Section: Development Of Kifs Targeting Inhibitorsmentioning
confidence: 99%